Assessing resistance of ivermectin and moxidectin against nematodes in cattle naturally infected using three different methodologies - Zanetti Lopes, Welber Daniel [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Soares, Vando Edesio [UNESP]; Santos, Thais Rabelo dos [UNESP]; Shigald de Matos, Lucas Vinicius [UNESP]; Favero, Flavia Carolina [UNESP]; Costa, Alvimar Jose da [UNESP] (Elsevier B.V., 2014)
The objective of this study was to evaluate the accuracy of the faecal egg count reduction test (FECRT) and the faecal egg count efficacy test (FECET) to assess the resistance status of ivermectin (630 mu g/g) and moxidectin (200 mu g/kg), using the controlled efficacy test as a reference, and whether the results of the EPG are equivalent to the efficacy results from the parasitological necropsies. Two experiments were conducted. The results demonstrate that it was not possible to demonstrate that the EPG values were equivalent with the ivermectin and moxidectin efficacy obtained by parasitological necropsies, mainly if the phenomenon of parasites resistance is not advanced in a determined field population. Maybe the FECET technique would be possibly better than the FECRT. The high anthelmintic efficacy of 200 mu g/kg moxidectin, in naturally infected cattle, against field population of nematodes that are resistant to 630 mu g/kg ivermectin, was observed in this study. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Anthelmintic; Cattle; Ivermectin; Moxidectin; Resistance